2014
DOI: 10.1021/la5033338
|View full text |Cite
|
Sign up to set email alerts
|

Ag-Nanoparticle-Decorated Ge Nanocap Arrays Protruding from Porous Anodic Aluminum Oxide as Sensitive and Reproducible Surface-Enhanced Raman Scattering Substrates

Abstract: We report on the fabrication of Ag nanoparticle (Ag NP) decorated germanium (Ge) nanocap (Ag-NPs@Ge-nanocap) arrays protruding from highly ordered porous anodic aluminum oxide (AAO) template as highly sensitive and uniform surface-enhanced Raman scattering (SERS) substrates. The hybrid SERS substrates are fabricated via a combinatorial process of AAO template-assisted growth of Ge nanotubes with each tube having a hemispherical nanocap on the AAO pore bottom, wet chemical etching of the remaining aluminum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…On the other hand, chemical enhancement accounts for a smaller enhancement, which results from the charge transfer between the molecules and the substrate. Recently, extensive investigations have demonstrated that additional Raman scattering enhancement arise from semiconductor (TiO 2 , ZnO, CdTe, Ge)‐Au (Ag) hybrid nanostructures, in which charge transfer occurs efficiently among them. The chemical mechanism is believed to contribute majorly to the observed large enhancement signals in these cases.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, chemical enhancement accounts for a smaller enhancement, which results from the charge transfer between the molecules and the substrate. Recently, extensive investigations have demonstrated that additional Raman scattering enhancement arise from semiconductor (TiO 2 , ZnO, CdTe, Ge)‐Au (Ag) hybrid nanostructures, in which charge transfer occurs efficiently among them. The chemical mechanism is believed to contribute majorly to the observed large enhancement signals in these cases.…”
Section: Introductionmentioning
confidence: 99%
“…[20] However, the HSCH 2 COOoccupied the active sites on the surface of the Ag particles, thereby weakening the SERS effect. Several kinds of nanomaterials including ZnO nanorod arrays, [21] carbon nanosheets, [22] germanium nanocap arrays, [23] ZnGa 2 O 4 nanoarrays, [24] SiO 2 nanofibers or nanospheres, [25][26] silicon nanowires, [27] TiO 2 nanoarrays, [28] vanadate microspheres, [29][30] polymer spheres and arrays, [31][32] graphitic petal arrays [33] have been used as templates to fabricate such hybrid nanostructures. [21][22][23][24][25][26][27][28][29][30][31][32][33] The hybrid nanostructure has advantages over the conventional pure bimetallic noble metal nanostructures, such as higher SERS activity, batter reproducibility and lower cost when used as SERS substrate.…”
Section: Introductionmentioning
confidence: 99%
“…FIGURE 4 | (A)Schematic for the fabrication of Ag-NPs @ Ge-nanocap arrays protruding from AAO template(Liu et al, 2014a); (B) Schematic illustration of nanoporous AAO-based multiplex vertical flow assay (VFA) for the detection of four inflammatory biomarkers with Raman dyes encoded core-shell SERS nanotags. Characteristic Raman peaks of NBA at 593 cm −1 , 4-MBA at 1,075 cm −1 , DNTB at 1,341 cm −1 , and MB at 1,621 cm −1 , are used to encode CRP, IL-6, SAA, and PCT, respectively(Chen et al, 2020).…”
mentioning
confidence: 99%